Attitudes towards Refugees from Ukraine in Poland with Special Consideration of Young Ukrainians in the Eyes of Polish Students, as Exemplified by the Olkusz Region - Kamionka, Mateusz (Acta Paedagogica Vilnensia, 2025)
After the outbreak of a full-scale war in Ukraine, thousands of children – refugees from Ukraine – appeared in Polish schools. On 1 September 2022, there were about 800,000 school-age children and teenagers from Ukraine in Poland. This caused changes in schools where, previously, the vast majority of students were Poles, especially in small towns and the countryside. Considering the above, the article will present the results of a pilot study from the town of Olkusz which can be called a ‘typical’ medium-sized Polish town. The qualitative research involved 280 young people aged 16–21. In the study, they were asked about their attitudes towards their friends from Ukraine and about their situation at school. The research is a pilot study; according to the author, the relationship between students from Poland and Ukraine in Polish schools has not yet been sufficiently explored. The results show that young people, despite their experience in helping Ukraine, are not particularly interested in contact with their peers from Ukraine and in their culture, but, on the other hand, they would not mind if their friend had a girlfriend or boyfriend from Ukraine. They also see that their Ukrainian friends have language problems, but there is no substantial language barrier between them. Research also shows the need for young people to learn about intercultural issues. Poland, accepting thousands of immigrants, like other Central European countries, must prepare for a gradual change in educational policy.
Keywords: Immigrant; Ukraine; refugees; school; intercultural education